New identification traits of Tracheliastes maculatus (Copepoda: Lernaeopodidae), a parasite of bream, Abramis brama (Cyprinidae) - Wojciech Piasecki; Geoffrey A. Boxshall; Remigiusz Panicz; Piotr Eljasik (International Journal for Parasitology: Parasites and Wildlife, 2025)
The parasitic copepod Tracheliastes maculatus Kollar, 1835, infects the freshwater bream, Abramis brama, a key species in European freshwater ecosystems. Despite its widespread occurrence and potential to cause skin hemorrhages, scale erosion and perforation, and fish mortality, species-level identification within the genus Tracheliastes has been problematic due to insufficient diagnostic traits. This study refines identification criteria by integrating morphological and genetic approaches. We present the first DNA barcode (COI gene sequence) for Tracheliastes maculaus, providing a molecular basis for taxonomic clarification. Additionally, scanning electron microscopy (SEM) reveals novel morphological details, including the number and distribution pattern of secondary denticles on endopodal Claw 1 of the antenna and structural differences in endopodal and exopodal side denticles of the antenna, both of which, may serve as new diagnostic features within the genus. Furthermore, we regard Tracheliastes mourkii as a nomen nudum because it was not morphologically diagnosed, and no museum specimen is extant. These findings improve species discrimination and set a benchmark for future taxonomic revisions of Tracheliastes, facilitating more precise ecological and parasitological assessments. A mini-review of the genus is also provided.